Dielectric behaviour of Hf-doped CaCu3Ti4O12 ceramics obtained by conventional synthesis and reactive sintering - de la Rubia, M. A. (2012)
CaCu3(Ti4−xHfx)O12 ceramics (x = 0.04, 0.1 and 0.2) were prepared by conventional synthesis (CS) and through reactive sintering (RS), in which synthesis and sintering of the material take place in one single step. The microstructure and the dielectric properties of Hf-doped CCTO (CCTOHf) have been studied by XRD, FE-SEM, AFM, Raman and impedance spectroscopy (IS) in order to correlate the structure, microstructure and the electrical properties. Samples prepared by reactive sintering show slightly higher dielectric constant than those prepared by conventional synthesis in the same way than the pure CCTO. Dielectric constant and dielectric losses decrease slightly increasing Hf content. For CCTOHf ceramics with x > 0.04 for CS and x > 0.1 for RS, a secondary phase HfTiO4 appears. As expected, the reactive sintering processing method allows a higher incorporation of Hf in the CCTO lattice than the conventional synthesis one.